2013
DOI: 10.1097/sla.0b013e31827017fc
|View full text |Cite
|
Sign up to set email alerts
|

The Overall Prevalence of Metastasis in T1 Esophageal Squamous Cell Carcinoma

Abstract: Our study provides a precise assessment of the comprehensive risk of metastasis and feasible predictive markers for T1 ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
128
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 34 publications
10
128
4
Order By: Relevance
“…Among 11 patients with additional CRT, three relapses (27%) were observed. These results were similar to the rate of the previous reports of 25-50% (6,13). Therefore, preceding ESD contributed to the reduction of the radiation dose and fields and prevented RT-related toxicities without increasing the relapse rate.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Among 11 patients with additional CRT, three relapses (27%) were observed. These results were similar to the rate of the previous reports of 25-50% (6,13). Therefore, preceding ESD contributed to the reduction of the radiation dose and fields and prevented RT-related toxicities without increasing the relapse rate.…”
Section: Discussionsupporting
confidence: 81%
“…Akutsu et al observed that when the tumor depth was ! SM 2, the patient had both a higher rate of lymph node involvement and also hematological recurrences, such as liver or lung metastases (13). Furthermore, their univariate and multivariate analyses showed that the tumor depth and presence of lymphatic and venous invasion were identified to be independent risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the multivariate analysis, in this study, sm3 and tumor location were strongly correlated with a worse overall survival rate. The depth of submucosal infiltration and lymphatic and venous invasion seemed to be an independent risk factor for LN metastases in a retrospective surgical study conducted on 295 patients with T1 esophageal squamocellular carcinoma [6]. A multicenter study that evaluated patients who were initially submitted to endoscopic resection of early esophageal adenocarcinoma (EAC) followed by esophagectomy, demonstrated that 24% of the patients with T1b tumors had positive LN [7].…”
Section: Early Esophageal Lesionsmentioning
confidence: 99%
“…Endoscopic submucosal dissection is a widely accepted procedure to curative treatment of SESCC limited to the epithelium or lamina propria mucosa (EP/LPM) because LN metastasis is rarely observed in these lesions [2][3][4]. However, LN metastasis is seen in approximately 10% of cases of SESCC with invasion into the muscularis mucosa or mildly into the submucosa (MM/SM1) and in approximately 40% with moderate or deep invasion into the submucosa (SM2/SM3) [5]. Therefore, MM/SM1 and SM2/SM3 SCCS are usually considered indications for surgery, chemoradiotherapy, or both.…”
Section: Introductionmentioning
confidence: 99%